Considering the action of frothers under degrading water quality - Tetlow, Sarah (Department of Chemical Engineering, 2020)
Froth flotation is a highly water-intensive process which is under scrutiny due to scarce fresh water supplies and increasingly strict environmental regulations with regards to polluted water discharge. This is driving the mining industry to use recycled water for their operations, which is usually sourced from tailings dams or concentrator thickeners. This means that the recycled water can contain elevated levels of dissolved solids which consist of various ions and other contaminants such as residual reagents. This presents a problem in the flotation circuit as these dissolved solids tend to affect the water quality and can impact the efficiency and performance of flotation operations. The stability of the froth is known to strongly affect flotation performance and thus the grade and recovery of the valuable minerals. Literature shows that both frothers and ions reduce bubble coalescence, and stabilise the bubbles that form, resulting in greater froth stability. Considering that the level of ions in process water is on the rise, and both variables act on the froth in a similar manner, it is becoming increasingly important to understand how frothers behave under conditions of increased ionic strength. If it can be determined how these variables interact, then it may be possible to manage frother dosage in operations that recycle process water with the aim of reducing the quantity and cost of frothers and limiting the need for large amounts of fresh water, while still maintaining flotation performance. Therefore, this study was undertaken to investigate how frother dosage and ionic strength, both individually and simultaneously, affect the froth stability and therefore flotation performance. This study was limited to varying the frother type, frother dosage and ionic strength whilst keeping all other experimental conditions constant. Batch flotation tests were carried out involving the bulk flotation of chalcopyrite and pentlandite. Flotation performance was evaluated by examining the water, solids, copper and nickel recoveries, and the grades of both copper and nickel. The ore used for this study was Kevitsa ore from Finland. Both the individual effects of frother dosage and ionic strength and their simultaneous action were analysed. It was found that increasing the frother dosage stabilised the froth and increased the recovery of water and solids but had no impact on the recovery of copper and only a slightly positive influence on the recovery of nickel. At the same time, the grades of both copper and nickel were found to decrease, likely due to increased gangue recoveries. Increasing the ionic strength also stabilised the froth which increased the recovery of water and solids, but both the recoveries and grades of copper and nickel were not significantly affected. Examining both variables simultaneously revealed that ionic strength was more influential than frother dosage in the recovery of water with the opposite being true for the solids recoveries. This means that a simultaneous increase in ionic strength and decrease in frother dosage by the same amount will increase the water recoveries and decrease the solids recoveries. It will also slightly decrease the nickel recoveries while having no effect on the copper recoveries. The grades of both will either increase or remain the same. Overall, managing the frother dosage under conditions of increased ionic strength, while still maintaining flotation performance, is possible and could result in a decrease in the quantity and cost of frothers required for flotation. It may also allow the mining industry to recycle more of their water without the need for extensive cleaning which in turn will reduce the amount of fresh water required for flotation and reduce environmental discharge. However, because ionic strength and frother dosage have varying levels of influence and therefore must be monitored, the amount by which the ionic strength of the water is allowed to increase, and the amount by which the frother dosage is decreased, need to be tailored to suit the needs of the plant with regards to water recovery and the recoveries and grades of the valuable minerals.